Techniques on vertical ridge augmentation: Indications and effectiveness - Urban, Istvan A.; Montero, Eduardo; Amerio, Ettore; Palombo, David; Monje, Alberto (Periodontology 2000, 2023)
Vertical ridge augmentation techniques have been advocated to enable restoring function and esthetics by means of implant‐supported rehabilitation. There are three major modalities. The first is guided bone regeneration, based on the principle of compartmentalization by means of using a barrier membrane, which has been demonstrated to be technically demanding with regard to soft tissue management. This requisite is also applicable in the case of the second modality of bone block grafts. Nonetheless, space creation and maintenance are provided by the solid nature of the graft. The third modality of distraction osteogenesis is also a valid and faster approach. Nonetheless, owing to this technique's inherent shortcomings, this method is currently deprecated. The purpose of this review is to shed light on the state‐of‐the‐art of the different modalities described for vertical ridge augmentation, including the indications, the step‐by‐step approach, and the effectiveness.